Cardi-Net: A deep neural network for classification of cardiac disease using phonocardiogram signal - Khan, Juwairiya Siraj; Kaushik, Manoj; Chaurasia, Anushka; Dutta, Malay Kishore; Burget, Radim (Computer methods and programs in biomedicine, 2022)
BACKGROUND AND OBJECTIVES: The lack of medical facilities in isolated areas makes many patients remain aloof from quick and timely diagnosis of cardiovascular diseases, leading to high mortality rates. A deep learning based method for automatic diagnosis of multiple cardiac diseases from Phonocardiogram (PCG) signals is proposed in this paper. METHODS: The proposed system is a combination of deep learning based convolutional neural network (CNN) and power spectrogram Cardi-Net, which can extract deep discriminating features of PCG signals from the power spectrogram to identify the diseases. The choice of Power Spectral Density (PSD) makes the model extract highly discriminatory features significant for the multi-classification of four common cardiac disorders. RESULTS: Data augmentation techniques are applied to make the model robust, and the model undergoes 10-fold cross-validation to yield an overall accuracy of 98.879% on the test dataset to diagnose multi heart diseases from PCG signals. CONCLUSION: The proposed model is completely automatic, where signal pre-processing and feature engineering are not required. The conversion time of power spectrogram from PCG signals is very low range from 0.10 s to 0.11 s. This reduces the complexity of the model, making it highly reliable and robust for real-time applications. The proposed architecture can be deployed on cloud and a low cost processor, desktop, android app leading to proper access to the dispensaries in remote areas.
Keywords: neuronové sítě; Data augmentation; Signal Processing, Computer-Assisted; Plant Extracts; kardiovaskulární nemoci; Phonocardiogram; počítačové zpracování signálu; Humans; Cardiac disorders; Cardiovascular Diseases; Neural Networks, Computer; lidé; rostlinné extrakty; Deep learning; nemoci srdce; Power spectrogram; Heart Diseases